New Fluorene Derivatives from Dendrobium gibsonii and Their α-Glucosidase Inhibitory Activity - May Thazin Thant (2020)
Two new compounds, dihydrodengibsinin (1) and dendrogibsol (2), were isolated from the whole plant of Dendrobium gibsonii, together with seven known compounds (3-9). The structures of the new compounds were elucidated by their spectroscopic data. All these isolates were evaluated for their α-glucosidase inhibitory activities. Dendrogibsol (2) and lusianthridin (7) showed strong α-glucosidase inhibitory activity when compared with acarbose. An enzyme kinetic study revealed that dendrogibsol (2) is a noncompetitive inhibitor of α-glucosidase.